In Vitro Metabolism of 3, 4-Methylenedioxymethamphetamine in Human Hepatocytes. (28th March 2014) - Ramaley, Corinne; Leonard, Susan C.; Miller, Jeffrey D.; Wilson, Denita Takesha-Mashia; Chang, Sai Y.; Chen, Qingyu; Li, Feng; Du, Chengan
Abstract: Users of the illicit drug, 3, 4-methylenedioxymethamphetamine (MDMA), show signs of neurotoxicity. However, the precise mechanism of neurotoxicity caused by use of MDMA has not yet been elucidated. Synthetic glutathione (GSH) conjugates of MDMA are transported into the brain by the GSH transporter and subsequently produce neurotoxicity. The objective of this research is to show direct evidence of the formation of GSH adducts of MDMA in human hepatocytes. High-performance liquid chromatography coupled with tandem mass spectrometry was utilized to examine in vitro incubations of MDMA with cryopreserved human hepatocytes. The use of hydrophilic liquid chromatography in combination with linear ion trap mass spectrometry permitted the identification of two possible GSH metabolites. Enhanced product ion scans of m / z = 499 and 487 amu of extracts from hepatocytes treated with 1.0 mM MDMA show a distinct fragmentation pattern ( m / z 194.2, 163, 135, 105), suggesting the formation of MDMA–GSH conjugate, MDMA-SG and 3, 4-dihydroxymethamphetamine-SG. The formation of an MDMA–GSH conjugate was further supported by the apparent lack of the same fragmentation pattern from hepatocyte samples without MDMA treatment. The results generated from this study yield valuable qualitative and quantitative information about the neurotoxic thioether metabolites formed from MDMA in humans.